autobase@collegemenfess, A Twitter Account Used as Information Retrieval Tool - Nanda Khaerunnisa Syafitri; Gema Rullyana; Ardiansah Ardiansah (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2020)
The development of technology and information has led to the emergence of many media that can be used as information sources, including social media. Twitter has started an automatic base (autobase) system with has automenfess feature. This study aims to see the level of users' ability and the use of autobase as an information retrieval system. Respondents were users or followers of the @collegemenfess Twitter account. This study used a quantitative approach with descriptive analysis. The data were obtained through an online survey of 70 followers of the @collegemenfess account. The study found that users' ability level was in the intermediate user category and the use of information retrieval system on this autobase was to send messages with a certain format which then that message will be a confession mention.